Intervenções pedagógicas e aprendizagem de matemática : implicações na consolidação da memória operacional - Silveira, Bruna Dorneles (2018)
This dissertation aims to verify how different strategies and pedagogical resources help in the consolidation of the operational memory contributing to the learning of Mathematics through the performance of the students participating in the research. The main question of the research is: How different resources and pedagogical strategies help in the consolidation of the operational memory contributing to the learning of Mathematics?. The participants of the research were eighty-five students from three groups that attended the 8th year of elementary school of a private school located in the Metropolitan Region of Porto Alegre - RS. For the data collection, two cognitive evaluations and questionnaires were used as instruments, both elaborated by the researcher and applied in all the students participating in the research. The research took place in three stages. The first one consisted in the development of the pedagogical interventions of the three proposals of teaching elaborated for the research, that emphasized: to the transmission and repetition; the manipulation of materials and the use of games; problem solving and the application of the first cognitive assessment soon after the end of each teaching proposal developed in the three classes of the research. In the second stage, the application of the cognitive evaluation after the period of five months of the end of the pedagogical interventions carried out with the classes. A qualitative analysis of each class is presented, prioritizing the individual performance and the collective performance related to the pedagogical interventions performed. From the numerical results, graphs and tables were elaborated with the pretension to illustrate the variations in the students performance in the evaluations applied in two different moments. The qualitative data were analyzed through the Discursive Textual Analysis - ATD. From this analysis, eight categories emerged in relation to the activities that contributed to the understanding of the contents developed, be they: pedagogical games; manipulative activities; learning by transmission; repetition of exercises; learning by interaction; content fixation. The results of the analysis allowed us to understand how the different pedagogical resources and strategies helped to store the information retained in the operational memory, through the analysis of the student performance in cognitive assessments and the perspectives of the participants expressed in the questionnaires applied. Thus, among the conclusions, it is pointed out that, from the perspective of students, participants in the research, the use of manipulative materials and pedagogical games contribute to the consolidation of operational memory, made explicit through the excerpts in the questionnaires and, obtained in the cognitive evaluations. It should also be noted that the groups that obtained better long-term performance converge with the developed teaching proposal. It is evidenced that the games used in the pedagogical interventions were effective for the consolidation of the operational memory, since they presented significant improvements in the students performances, contributing to the learning of Mathematics.